Five ways to get a grip by incorporating trust into the design and implementation of peer coaching programs - Bell, Adriane E; Meyer, Holly S; Maggio, Lauren A; Anderson, LaKesha N (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Peer coaching is a form of faculty development in which faculty improve their teaching skills through collaborative work or peer observation of teaching. As a tool grounded in experiential learning, peer coaching promotes targeted feedback, reflection on action, and collegial exchange to improve teacher self-efficacy and trainee learning outcomes. Nevertheless, faculty developers face challenges in creating sustainable, effective peer coaching programs as faculty fear scrutiny of their teaching practices. Additionally, to promote collegial exchange, faculty (the person observed and peer coach) must trust one another and accept vulnerability. Without attending to trust, faculty developers may find themselves on black ice, designing and implementing ineffective peer coaching programs. In this Black Ice article, we underscore the role of trust in peer coaching and present five ways to help faculty developers get a grip by incorporating trust into the design and implementation of peer coaching programs, optimizing its efficacy.